Patients with psoriasis have an increased amount of epicardial fat tissue. (1st March 2014) - Balci, A.; Celik, M.; Balci, D. D.; Karazincir, S.; Yonden, Z.; Korkmaz, I.; Celik, E.; Egilmez, E.
Summary: Background: Psoriasis is associated with coronary artery disease, and ischemic heart disease is associated with increased amounts of epicardial fat tissue (EFT). There has as yet been no study published on the accumulation of EFT in patients with psoriasis. Aim: To compare epicardial fat accumulation and coronary artery calcium score (CACS) in patients with psoriasis and controls. Methods: We enrolled 38 patients with psoriasis and 38 controls matched for age and gender. Epicardial fat area (EFA) and CACS were evaluated by multidetector computed tomography. Results: Mean EFA in patients with psoriasis was significantly higher than in controls (13.8 ± 8.4 vs. 9.7 ± 6.4 cm 2, respectively, P = 0.02), but mean CACS did not differ significantly between the two groups (55.2 ± 65.4 vs. 27.8 ± 29.3; P > 0.05). Multiple linear regression analyses indicated that EFA was significantly associated with waist circumference and presence of coronary artery calcification in both patients and controls, whereas EFA was significantly associated waist circumference and age in patients only ( P < 0.05). Conclusions: Patients with psoriasis had a higher level of EFA compared with controls, and EFA was independently associated with the presence of CAC in all study subjects.